Eco-nursing competencies for nurses: A scoping review - Thandazile Sibindi; Jennifer-Anne Chipps; Talitha Crowley (Elsevier, 2024)
Background: Nurses are tasked with addressing the health impacts of climate change. Eco-nursing competencies, covering knowledge, attitudes, and skills related to climate change, equip nurses to actively mitigate and adapt to its effects on health and the environment. Objective: To synthesize existing literature on eco-nursing roles and competencies for nurses. Methods: A scoping review of published papers examined nurses' roles and eco-nursing competencies. Databases searched included Academic Search Complete, CINAHL Plus, MEDLINE (PubMed), and Google Scholar. Search terms encompassed climate change and nursing synonyms, limited to English articles up to April 15, 2023. Thematic analysis was used to synthesize findings, delineating roles, and eco-nursing competencies. Results were tabulated. Results: Out of 445 papers identified, 31 underwent data analysis. These papers highlighted nurses' roles in climate change (42%), along with climate change knowledge and skills (64.5%), and attitudes (13%). Roles encompassed research, education, advocacy, leadership, and clinical practice, with corresponding competencies embedded within existing core competencies for general nurses, nurse specialists, and nurse managers. Conclusion: The review demonstrates that nurses' roles in climate change necessitate relevant knowledge, attitudes, and skills. Future research should contextualize these roles and eco-nursing competencies based on geographical locations, considering the distinct disease burden in each area. Registration: The study protocol was registered in the Open Science Framework on 5 March 2023 before conducting the full study https://doi.org/10.17605/OSF.IO/9GC4N Tweetable abstract: Amidst growing concerns about climate change, nurses are increasingly tasked with preparing to mitigate its health impacts through the delineation of eco-nursing competencies. These competencies will equip nurses to effectively tackle the health and environmental ramifications of climate change, building upon existing core competencies tailored to various geographic contexts.